2010
DOI: 10.1074/jbc.m109.086330
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Substrate Recognition and Insight into Feedback Inhibition of Homocitrate Synthase from Thermus thermophilus

Abstract: Homocitrate synthase (HCS) catalyzes aldol-type condensation of acetyl coenzyme A (acetyl-CoA) and ␣-ketoglutarate (␣-KG) to synthesize homocitrate (HC), which is the first and committed step in the lysine biosynthetic pathway through ␣-aminoadipate. As known in most enzymes catalyzing the first reactions in amino acid biosynthetic pathways, HCS is regulated via feedback inhibition by the end product, lysine. Here, we determined the crystal structures of HCS from Thermus thermophilus complexed with ␣-KG, HC, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
51
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(52 citation statements)
references
References 43 publications
1
51
0
Order By: Relevance
“…Collectively, our structural and functional data demonstrate that L-lysine competes with 2-OG for binding to SpHCS, in agreement with prior studies of HCS from P. chrysogenum (10), T. thermophilus (11,12), and S. cerevisiae (9). The inherent plasticity of the active site of the enzyme enables differential recognition of 2-OG and L-lysine.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Collectively, our structural and functional data demonstrate that L-lysine competes with 2-OG for binding to SpHCS, in agreement with prior studies of HCS from P. chrysogenum (10), T. thermophilus (11,12), and S. cerevisiae (9). The inherent plasticity of the active site of the enzyme enables differential recognition of 2-OG and L-lysine.…”
Section: Discussionsupporting
confidence: 76%
“…4). In very recent studies, the structure of T. thermophilus HCS in complex with L-lysine was reported (12). This enzyme displays an inhibitor binding mode that is essentially identical to that of SpHCS, illustrating structural conservation throughout evolution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lysine at M levels inhibits HCS of T. thermophilus (8). As in the instances described above, it is possible that the growth inhibition of T. thermophilus by AEC is due to the inhibition of HCS; however, we also found that the growth of a T. thermophilus mutant possessing HCS with H72L replacement, which is feedback resistant to high concentrations of lysine (9), was inhibited by AEC with the same sensitivity as that of the wild-type strain. This observation suggests that AEC acts on a target other than HCS to inhibit the growth of T. thermophilus.…”
mentioning
confidence: 46%
“…However, in T. thermophilus, lysine is synthesized via the ␣-aminoadipate pathway. Crystal structures of TtHCS have recently been solved (10), but a detailed study of the kinetic and/or chemical mechanism of TtHCS has not been carried out. In this article, the TtHCS has been subjected to initial rate and isotope effect studies, and the pH dependence of kinetic parameters has been measured.…”
mentioning
confidence: 99%